Synthesis of chiral mono(N-heterocyclic carbene) palladium and gold complexes with a 1,1'-biphenyl scaffold and their applications in catalysis - Liu, Lian-jun; Wang, Feijun; Wang, Wenfeng; Zhao, Mei-xin; Shi, Min (Beilstein Journal of Organic Chemistry, 2011)
Axially chiral mono(NHC)–Pd(II) and mono(NHC)–Au(I) complexes with one side shaped 1,1'-biphenyl backbone have been prepared from chiral 6,6'-dimethoxybiphenyl-2,2'-diamine. The complexes were characterized by X-ray crystal structure diffraction. The Pd(II) complex showed good catalytic activities in the Suzuki–Miyaura and Heck–Mizoroki coupling reactions, and the (S)-Au(I) complexes also showed good catalytic activities in the asymmetric intramolecular hydroamination reaction to give the corresponding product in moderate ee.
Keywords: chiral mono(N-heterocyclic carbene) complex; Heck–Mizoroki reaction; hydroamination; Suzuki–Miyaura reaction